Fondements théoriques et méthodologiques de la recherche-intervention : communication et démocratie dans des organisations sociosanitaires - Isabelle Ruelland; Jacques Rhéaume (Communiquer, 2020)
The article offers a reflection on spaces for dialogue created or observed during intervention-research carried out within health and social organizations. More broadly, it is a question of understanding how intervention-research contributes to the democratization of human communications in organizations. How they allow actors to be included in the organization by creating communications leading to the empowerment of individuals occupying poorly recognized different positions. A few references in philosophy make it possible to shed light on the links between democracy, organization, communication and intervention in order to better situate the development of a critical perspective of approaches in intervention-research within organizations. Finally, based on examples of research carried out in socio-health organization in Quebec and Brazil, we discuss the strengths and limits of research practices focusing on the space for dialogue.